Methane emissions among individual dairy cows during milking quantified by eructation peaks or ratio with carbon dioxide - Bell, Matthew J.; Saunders, N.; Wilcox, R.H; Homer, Elizabeth; Goodman, J.R.; Craigon, J.; Garnsworthy, P.C. (American Dairy Science Association, 2014)
The aims of this study were to compare methods for examining measurements of CH4 and CO2 emissions of dairy cows during milking and to assess repeatability and variation of CH4 emissions among individual dairy cows. Measurements of CH4 and CO2 emissions from 36 cows were collected in 3 consecutive feeding periods. In the first period, cows were fed a commercial partial mixed ration (PMR) containing 69% forage. In the second and third periods, the same 36 cows were fed a high-forage PMR ration containing 75% forage, with either a high grass silage or high maize silage content. Emissions of CH4 during each milking were examined using 2 methods. First, peaks in CH4 concentration due to eructations during milking were quantified. Second, ratios of CH4 and CO2 average concentrations during milking were calculated. A linear mixed model was used to assess differences between PMR. Variation in CH4 emissions was observed among cows after adjusting for effects of lactation number, week of lactation, diet, individual cow, and feeding period, with coefficients of variation estimated from variance components ranging from 11 to 14% across diets and methods of quantifying emissions. No significant difference was detected between the 3 PMR in CH4 emissions estimated by either method. Emissions of CH4 calculated from eructation peaks or as CH4 to CO2 ratio were positively associated with forage dry matter intake. Ranking of cows according to CH4 emissions on different diets was correlated for both methods, although rank correlations and repeatability were greater for CH4 concentration from eructation peaks than for CH4-to-CO2 ratio. We conclude that quantifying enteric CH4 emissions either using eructation peaks in concentration or as CH4-to-CO2 ratio can provide highly repeatable phenotypes for ranking cows on CH4 output.